Malic acid complex method for preparation of LiNiVO4 nano-crystallites - Thongtem T. (2014)
LiNiVO4 nano-crystallites were prepared by the polymerized complex method using Li2CO3, Ni(CH3COO) 2•4H2O and NH4VO3 as starting reagents and malic acid as a complexing agent. With the subsequent calcination at 450°C, the powder analyzed by XRD, FTIR, Raman, electron diffraction, SEM and TEM techniques was found to be inverse spinel LiNiVO4 with ~20nm in diameter. TGA shows continuous weight loss at 40-450°C due to the evaporation and decomposition processes. Above 450°C, weight percent tended to be constant. In addition, formation mechanism of the purified LiNiVO 4 was proposed to relate with the experimental results. © Springer Science+Business Media, LLC 2007.